Comparison of Bond Strength of a Pressed Ceramic Fused to Metal versus Feldspathic Porcelain Fused to Metal - Daniel M. Schweitzer, DDS;1 Gary R. Goldstein, DDS;2 John L. Ricci, PhD;3 (Journal of Prosthodontics, 2005)
To compare the debonding/crack initiation strength (D/CIS) of a low-fusing pressable leucite-based glass ceramic (PC) fused to metal to a feldspathic porcelain (FP) fused to metal.